Quantitative Flavonoids and Antioxidant Profiles by DPPH Assay of Centella Asiatica Serum Cosmetic Products Versus Ethanol Extract - Habibie, Sutan Farrell; Dwijayanti, Adisti; Fachri, Wilzar (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2025)
The cosmetic industry is currently leaning toward herbal skincare products due to strong consumer preference for natural ingredients. Centella asiatica (CA) is frequently used as it contains flavonoids and centelloids known for their beneficial antioxidant properties. This study aimed to assess the efficacy of CA extract when incorporated into cosmetic formulations by comparing the total flavonoid content (TFC) and antioxidant activity of five commercial serums (A-E) against a pure CA ethanol extract. The experimental study was conducted in vitro, utilizing the CA extract, Vitamin C (as a positive control), and the five commercial serum products. TFC was determined quantitatively using UV-Visible spectrophotometry and quercetin standard. Antioxidant activity was measured using DPPH assay to calculate the IC50 value. Pure CA extract showed a mean TFC of 37.10 ± 0.21 mg QE/g, with serum samples showing high variability; the highest being Sample C with a TFC of 216.6 (99.89 - 246.1) mg QE/g and the lowest being sample E with a TFC of 24.75 ± 1.88 mg QE/g. Crucially, the pure CA extract demonstrated strong antioxidant activity with a mean IC50 of 52.45 ± 4.96 ppm. In contrast, all serum products exhibited significantly weaker antioxidant activities. Samples C and D resulted in extremely high IC50 values of 244100 ± 116700 ppm and 319300 ± 95700 ppm respectively, categorized as lower than weak, while samples A, B, and E were unable to reach 50% inhibition, indicating an antioxidant capacity below the measurable range. In conclusion, despite the pure Centella asiatica ethanol extract showing robust antioxidant activity, the commercial cosmetic serums demonstrated a significantly lower range of activity and highly inconsistent TFC, suggesting that the raw extract's potency does not reliably transfer to the final product formulation.